2023
DOI: 10.1155/2023/5126825
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clinically Indicated Liraglutide on Pericoronary Adipose Tissue in Type 2 Diabetic Patients

Abstract: Vascular inflammation can be detected in the pericoronary adipose tissue (PCAT) by coronary computed tomography angiography (CCTA) attenuation. Treatment with liraglutide is associated with anti-inflammatory effects and reduces cardiovascular risk in diabetic patients. This study is aimed at examining the effect of clinically indicated liraglutide on PCAT attenuation. Asymptomatic patients with type 2 diabetes mellitus (T2DM) and without known ischemic heart disease underwent clinical examination, blood analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…More recently, Biesenbach et al showed that, in multivariable linear regression analysis, liraglutide treatment was associated with lower PCAT attenuation values around the LAD artery when adjusted for age, sex, BMI, and T2D duration ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Biesenbach et al showed that, in multivariable linear regression analysis, liraglutide treatment was associated with lower PCAT attenuation values around the LAD artery when adjusted for age, sex, BMI, and T2D duration ( 22 ).…”
Section: Discussionmentioning
confidence: 99%